LECTURERS’ CLASSROOM DISCOURSE EVENTS AND POWER RELATION USED IN COMMUNICATING LEARNING TASKS - Yelfiza Yelfiza (Universitas Negeri Padang, 2016)
This study is proposed to find out lecturers’ discourse event in communicating learning tasks. There are two research questions formulated in this research. They are types of events of the discourse and the power relation of each event. The method of the research is content analysis. The research participants were chosen purposively, based on consideration of the subjects they taught; Research in Language Teaching, Classroom Management, Speech, Translation, and Paper/r Thesis Writing. The other participants were the students who studied with the lecturers. Data were gathered by recording the process of learning. They were analyzed by using textual analysis. Findings of the research show that the lecturers’ classroom discourse has 9 types of events, namely 1) preparing before discussion, 2) confirming, 3) giving comment on the students’ work and respond to the student’s question, 4) commanding, 5) directing, 6) encouraging, 7) giving information about tasks, 8) rereading materials and commanding, and 9) discussing. Meanwhile, the power relation is categorized into two forms, namely lecturer’s domination and equal function between the lecturer and the students. The lecturer and the students have equal power in encouraging and discussing events, but they do not have it in the other events. Based on the findings, lecturers are recommended to use the discourse in which the lecturer and the students have equal power in producing the discourse.